Train-bridge system dynamics analysis with uncertain parameters based on new point estimate method. (15th November 2019) - Jiang, Lizhong; Liu, Xiang; Xiang, Ping; Zhou, Wangbao
Highlights: Vibration of train-bridge couple system with random parameters is calculate. The efficiency and accuracy of NPEM in train-bridge couple vibration is evaluated. Response with random parameter and different coefficient of variation is discussed. Abstract: In the analysis of train-bridge coupled vibration system, randomness of parameters of high-speed railway bridge cannot be ignored. The new point estimate method (NPEM) is a kind of accurate and efficient method to calculate the random response and reliability. In this paper, NPEM is applied to analyze the random dynamic responses of 3D train-bridge coupled system with random parameters, including parameters of bridge materials, environment factor and prestressing parameters. Newmark-β approach is applied as the integration algorithm, and the Monte Carlo method is used to validate the feasibility of the NPEM. The results show that NPEM can be combined with random system accurately and efficiently. Furthermore, the influences of different random parameters distributions are discussed.